EVALUASI KINERJA MESIN DIESEL BERDASARKAN ANALISIS INDICATED HORSE POWER (IHP) - Moch. Syaiful Anwar; Mochamad Shaleh (Universitas Majalengka, 2025)
This research evaluates the performance of a diesel engine based on the analysis of Indicated Horse Power (IHP) using the Pressure Combustion Analysis (PCA) method. The study applied a quantitative descriptive approach by measuring combustion pressure in each cylinder under stable operating conditions. Data acquisition was carried out using the Haliza Machinery & Diesel Engine Analyzer combined with SoftHaliza software for processing combustion characteristics and engine performance parameters. The investigation focused on several variables, including combustion pressure, ignition delay, pressure at crank angle 340°, combustion stability, and IHP distribution among cylinders. The results indicated that the combustion process in all cylinders operated under normal conditions with relatively stable pressure patterns. No significant abnormalities such as excessive ignition delay, combustion instability, or diesel knocking were identified during testing. The analysis also showed that the total Indicated Horse Power generated by the engine reached 1730.3 kW, equivalent to approximately 87% of the generator output capacity of 4000 kW. In addition, the uniformity of combustion pressure among cylinders demonstrated that the fuel injection and combustion systems were functioning properly. Overall, the PCA method proved effective for monitoring combustion characteristics and evaluating diesel engine performance. The method can therefore be implemented as part of a predictive maintenance strategy to improve operational reliability, combustion efficiency, and engine durability in diesel power generation systems.